2021
DOI: 10.5603/fhc.a2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA attenuates high glucose-induced epithelial-to-mesenchymal transition in HK-2 cells through VDR/Wnt/β-catenin signaling pathway

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Histochemica et Cytobiologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Recently, STAT5 was reported to play a crucial role in the susceptibility to diabetes pathologies, 10 and participated in modulation of epithelial‐to‐mesenchymal transition 11 . And high glucose treatment could mediate epithelial‐mesenchymal transition in tubulointerstitial and proximal tubular cells 21,22 . This work indicated that high glucose/hyperglycemia increased STAT5A levels in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, STAT5 was reported to play a crucial role in the susceptibility to diabetes pathologies, 10 and participated in modulation of epithelial‐to‐mesenchymal transition 11 . And high glucose treatment could mediate epithelial‐mesenchymal transition in tubulointerstitial and proximal tubular cells 21,22 . This work indicated that high glucose/hyperglycemia increased STAT5A levels in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 79%
“…11 And high glucose treatment could mediate epithelial-mesenchymal transition in tubulointerstitial and proximal tubular cells. 21,22 This work has some limitations, which may be future directions.…”
Section: Discussionmentioning
confidence: 99%
“…α-SMA is a specific marker of interstitial cells, which is expressed at a low level in normal tissues and organs but upregulated in tissues or cells during interstitial transdifferentiation. Studies have shown that the level of α-SMApositive expression is positively correlated with the degree of tissue fibrosis, and a large amount of α-SMA expression is a marker of epithelial and mesenchymal cell transformation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA was demonstrated to have excellent anti-fibrotic properties in streptozotocin-induced and 5/6 nephrectomy models, respectively ( Ahn et al, 2010 ; Xu et al, 2020 ). More importantly, the mechanism for SM against renal fibrosis might be related to reducing endoplasmic reticulum stress to attenuate PERK signaling activities, decreasing expressions of Ang II, TGF-β1 and collagen IV, attenuating high glucose-induced EMT by up-regulating VDR levels on Wnt/β-catenin pathway and inhibiting HG-induced the epithelial-myofibroblast trans differentiation pathway ( Ahn et al, 2010 ; Cao et al, 2017 ; Xu et al, 2020 ; Zeng and Bao, 2021a ).…”
Section: Pharmacological Actions Of Salvia Miltiorrhiza ...mentioning
confidence: 99%